Biodesulfurization enhancement via targeted re-insertion of the flavin reductase dszD in the genome of the model strain Rhodococcus qingshengii IGTS8 - Olga Martzoukou; Fotios Klenias; Eleni Kopsini; Dimitris G. Hatzinikolaou (Heliyon)
Biodesulfurization (BDS) has emerged as an alternative to the excessively costly hydrodesulfurization of recalcitrant heterocyclic sulfur compounds, such as dibenzothiophene (DBT) and its derivatives. The model desulfurizing strain Rhodococcus qingshengii IGTS8 is responsible for the removal of sulfur through the 4S metabolic pathway, operating through a plasmid-borne dszABC operon, as well as the chromosomal gene for the flavin reductase, dszD. However, naturally occurring biocatalysts do not exhibit the required BDS activity to be useful for industrial applications and for this reason, genetic modifications are currently being explored. Here, we constructed a genetically modified R. qingshengii IGTS8 strain, which carries an additional copy of the flavin reductase gene dszD under the control of the rhodococcal promoter Pkap1, inserted in the neutral chromosomal genetic locus crtI. We conducted a comparative study of the growth and biodesulfurization capabilities of Pkap1-dszD, wild-type and crtIΔ strains, grown on different types and concentrations of carbon and sulfur sources. A significant enhancement of biodesulfurization activity, maximum calculated biomass, and dszD transcript levels in the presence of DBT as the sole sulfur source was achieved for the Pkap1-dszD strain paving the way for further studies that could lead to a more viable commercial biodesulfurization process.